1983
DOI: 10.1203/00006450-198305000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Production to Milk Proteins in the Jejunal Mucosa of Children with Cow's Milk Protein Intolerance

Abstract: Summary A direct immunofluorescent technique with fluorescein-labeledantigens was used to examine the jejunal mucosa for specific antibody production in 23 children aged 2-25 months referred for diagnostic biopsy. Plasma cells containing antibodies to p-lactoglobulin (PLG) or bovine serum albumin (BSA) were present in I1 of 16 biopsies from patients with cow's milk protein intolerance (CMPI) but only one of eight controls, all on a diet containing cow's milk. Antibody-containing cells (ACC) constituted approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Circumstantial evidence that intact food proteins or peptide fragments cross the gut barrier is offered by the presence in normal individuals of antibodies to a wide range of food proteins, such as b-lactoglobulin (b-Lg), in the circulation [5] and the jejeunal mucosa [6]. The presence of proteins, such as ovalbumin, in the blood of individuals after consumption of egg, also supports the premise that intact proteins, albeit in small quantities, can enter the body [7].…”
Section: Digestion Of Allergensmentioning
confidence: 99%
“…Circumstantial evidence that intact food proteins or peptide fragments cross the gut barrier is offered by the presence in normal individuals of antibodies to a wide range of food proteins, such as b-lactoglobulin (b-Lg), in the circulation [5] and the jejeunal mucosa [6]. The presence of proteins, such as ovalbumin, in the blood of individuals after consumption of egg, also supports the premise that intact proteins, albeit in small quantities, can enter the body [7].…”
Section: Digestion Of Allergensmentioning
confidence: 99%
“…Further evidence in favor of the argument that IgE in feces is represented by such a resistant fragment is our find ing that a trypsin inhibitor did not influence the IgE concentrations when added to fresh feces. It is, there fore, unlikely that fecal IgE excreted into the gut lu men from the IgE-containing plasma cells which re side in the gut mucosa [3,II,12], had been falsely re duced because of rare passages of stools.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that diarrhea in itself will not lead to significantly in creased fecal IgE concentrations [12], The diarrhea of several of the ascaris-infected children could there fore not explain the findings. Thus, it seems that the ascaris worm, like some food allergens [20], can elicit a marked IgE response in the gut.…”
Section: Discussionmentioning
confidence: 99%